Distributed education enables distributed economic impact: The economic contribution of the Northern Ontario School of Medicine to communities in Canada - John C. Hogenbirk; David Robinson; Roger P. Strasser (Health Economics Review, 2021)
Background: Medical schools with distributed or regional programs encourage people to live, work, and learn in communities that may be economically challenged. Local spending by the program, staff, teachers, and students has a local economic impact. Although the economic impact of DME has been estimated for nations and sub-national regions, the community-specific impact is often unknown. Communities that contribute to the success of DME have an interest in knowing the local economic impact of this participation. To provide this information, we estimated the economic impact of the Northern Ontario School of Medicine (NOSM) on selected communities in the historically medically underserviced and economically disadvantaged Northern Ontario region. Methods: Economic impact was estimated by a cash-flow local economic model. Detailed data on program and learner spending were obtained for Northern Ontario communities. We included spending on NOSM's distributed education and research programs, medical residents' salary program, the clinical teachers' reimbursement program, and spending by learners. Economic impact was estimated from total spending in the community adjusted by an economic multiplier based on community population size, industry diversity, and propensity to spend locally. Community employment impact was also estimated. Results: In 2019, direct program and learner spending in Northern Ontario totalled 64.6 M (million) Canadian Dollars. Approximately 76% (49.1 M) was spent in the two largest population centres of 122,000 and 165,000 people, with 1-5% (0.7 M - 3.1 M) spent in communities of 5000-78,000 people. In 2019, total economic impact in Northern Ontario was estimated to be 107 M, with an impact of 38 M and 36 M in the two largest population centres. The remaining 34 M (32%) of the economic impact occurred in smaller communities or within the region. Expressed alternatively as employment impact, the 404 full time equivalent (FTE) positions supported an additional 298 FTE positions in Northern Ontario. NOSM-trained physicians practising in the region added an economic impact of 88 M. Conclusions: By establishing programs and bringing people to Northern Ontario communities, NOSM added local spending and knowledge-based economic activity to a predominantly resource-based economy. In an economically deprived region, distributed medical education enabled distributed economic impact.
Keywords: 330; Distributed medical education; Economic impact; Economic contribution; Socio-economic deprivation; Social accountability; Underserviced areas; Ontario; Canada